1992
DOI: 10.1177/030802269205500207
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Occupational Therapy in the Context of the American Influence on the Profession: Part 2

Abstract: This article presents an overview of the genesis of the beliefs and values about occupational therapy as they emerged in the USA, reviews some of the factors associated with these developments, and questions the professional relevance of the concept of occupation as promulgated in the model of human occupation. Part 1 provided the background: it offered an historical outline of the beginning of occupational therapy in the USA, by reflecting on the meaning of occupation and by evaluating the concept of occupati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

1995
1995
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
7
0
5
Order By: Relevance
“…Darnell (2002) pointed out that the concept of occupation is ethnocentric and far from universal. Mocellin (1992) questioned the applicability of the concept of competence and mastery.…”
Section: Culture and Occupational Therapy Practicementioning
confidence: 99%
“…Darnell (2002) pointed out that the concept of occupation is ethnocentric and far from universal. Mocellin (1992) questioned the applicability of the concept of competence and mastery.…”
Section: Culture and Occupational Therapy Practicementioning
confidence: 99%
“…Occupational therapy models appear to have been have developed exclusively in the Western world (Mocellin, 1992). The author questions what will happen when these models are applied in other cultures.…”
Section: Resultsmentioning
confidence: 99%
“…He recognised the need for new models to be developed to cover those areas of clinical concern that were inadequately addressed by existing models of practice. Mocellin (1992), for his part, suggested that 'there are real problems associated with the universal acceptance and applicability of a CUlture-specific clinical model of practice' (p55).…”
Section: Discussionmentioning
confidence: 99%